PENGARUH PENYULUHAN KESEHATAN TENTANG HIV/AIDS TERHADAP PENGETAHUAN DAN SIKAP WANITA BINAAN DI PANTI SOSIAL KARYA WANITA ANDAM DEWI KABUPATEN SOLOK - Rahmawati, Lisa; Hayati, Neni Fitra; Ningsih, Mahdalena Prihatin; Sofia, Tri Mira (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Indonesia is the country with the fastest transmission of HIV/AIDS in Southeast Asia. From its first discovery in 1987 until June 2019, HIV/AIDS has been reported by 463 (90.07%) districts/cities in Indonesia. The lack of knowledge and attitudes of the foster women towards health behaviors about HIV/AIDS becomes the cause of the increasing number of people with HIV/AIDS in West Sumatra Province. One way to reduce the incidence of HIV/AIDS is by providing health education. This study aims to determine the effect of health education on HIV/AIDS on women’s knowledge and attitudes in PSKW Andam Dewi Solok Regency. This type of research is a quasi-experiment with one group pretest-posttest design. June 5-9, 2020, data collection was carried out in the Hall of PSKW Andam Dewi. The population in this study were all fostered women totaling 40 people, and all of them were sampled, namely 40 people. The data collection was conducted using a questionnaire method. Univariate and bivariate analysis was used in the data processing techniques of editing, coding, entry, tabulating, and cleaning with a dependent t-test. The study results showed that the average knowledge before and after counseling was 14.08 and 18.22, respectively. The results of mean attitude before and after counseling was 89.05 and 111.80, respectively. The statistical test results found that there was an influence of health education about HIV/AIDS on knowledge (p-value 0.000) and attitudes (p-value 0.000) of women under the guidance of PSKW Andam Dewi. This research concludes that health education affects the knowledge and attitudes of the target women. For this reason, it is suggested that PSKW Andam Dewi continue to provide health education on HIV/AIDS on an ongoing basis using the lecture method with power point and video media.